Life Cycle Assessment-Based Approach to Forecast the Response of Waste Management Policy Targets to the Environment - Kavals Edgars (Sciendo, 2021)
Inadequate municipal waste management, associated with a dominance of waste landfilling and low efficiency of resource and energy recovery, is the major challenge towards circular economy targets for some European Union countries, including Latvia. The aim of the study is to evaluate environmental performance from implementation of waste management policy goals in waste management systems of Latvia applying life cycle assessment methodology. The waste management system in Latvia was evaluated for two scenarios: baseline situation (based on statistical data from 2016) and future scenario – 2030. Baseline scenario assessment results show the existing material and energy recovery potential from municipal solid waste generated in Latvia. Meanwhile, results obtained from the 2030 scenario demonstrated that boosting recovery rates of plastic by 20 % and organic waste by 20 % can contribute to the minimization of life cycle environmental impacts (human health, resources, climate change, ecosystems) by 1.8 % and organic by 3.6 % correspondingly.